If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h * 1(x) = h(x) Reorder the terms for easier multiplication: 1h * x = h(x) Multiply h * x 1hx = h(x) Multiply h * x 1hx = hx Solving 1hx = hx Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1hx' to each side of the equation. 1hx + -1hx = hx + -1hx Combine like terms: 1hx + -1hx = 0 0 = hx + -1hx Combine like terms: hx + -1hx = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| -v+231=57 | | Q=5x+20 | | hg(1)=h(1) | | 3-6r=-39 | | 1275=(X+20)17 | | 63=160-u | | 10+4x+2y=36 | | (3n)/2=3 | | 19-p=3p-p | | 10x+5y=36 | | 22.50+17.50x=83.75 | | 88=-x+249 | | 3(6x+6)=3(8x+6) | | -4x+44=64 | | 6x^2-3=2x+6 | | -73-4x/3 | | 1n(30x+2)=1n(-2+66) | | 4(3p-5)= | | k=bx | | 29=y+20 | | 42364362436=43x-54-35245*432 | | hg(x)=h(x) | | R=10-9r | | 20+2x=134 | | 3n=3/2 | | 2x+7x-2+5x=180 | | b+2b-10=10(b+5)+15+b | | 6(8n-4)=4(2n-6) | | 3*n=3 | | 9+8y=6y-5 | | -8(x-3.6)=36 | | 3-12y=11-5y |